A comprehensive experimental and theoretical study on BN nanosheets for the adsorption of pharmaceutical drugs. (24th February 2020) - Goyal, Ankita; Aggarwal, Diksha; Kapoor, Surbhi; Goel, Neetu; Singhal, Sonal; Shukla, Jaya
Abstract : BN nanosheets were explored as proficient adsorbents for pharmaceutical drugs owing to high adsorption capacity and favorable interactions. Abstract : BN nanomaterials have revolutionized the scientific world with their outstanding physiochemical properties leading to far-fetched applicability in the field of adsorption. In this context, the present investigation dealt with the synthesis and characterization of BN nanosheets and their applicability for the adsorption of pharmaceutical drugs. BN nanosheets have exhibited excellent adsorption for levofloxacin, tetracycline, and curcumin. To get further insights into the feasibility of the adsorption of drugs over BN nanosheets and to scrutinize the interactions between the two, computations were performed within DFT formalism. The theoretical investigations unveiled the presence of hydrogen bonding and negative adsorption energies liable for favorable adsorption. The synthesized BN nanosheets had good biocompatibility and were proven to be proficient adsorbents for the sustainability of the environment.